Isolated Syndesmotic Fixation is Associated with Increased Risk of Arthrodesis and Arthroplasty Operations Compared to Nonoperatively Managed Syndesmotic Injury: A Propensity-Scored Analysis - Sean Sequeira MD; Heath P. Gould MD; Walter C. Hembree MD (Foot & Ankle Orthopaedics)
Category: Trauma; Sports Introduction/Purpose: Disruption of the distal tibiofibular syndesmosis can occur concomitantly with ankle fracture or as an isolated soft tissue injury. Although syndesmotic fixation is effective in providing stability to the distal tibiofibular joint, biomechanical studies suggest that over-reduction of the syndesmosis may increase ankle contact pressures and potentially accelerate tibiotalar joint degeneration in the longer term. The purpose of this investigation was to evaluate reoperation rates in patients with isolated syndesmotic disruption who underwent fixation versus those who were managed nonoperatively. Methods: A large, nationwide insurance database was retrospectively reviewed to identify all patients who were diagnosed with an isolated distal tibiofibular syndesmotic injury (without concomitant fracture) between 2010 and 2019. Patients who underwent surgical stabilization were matched using a propensity scoring algorithm to patients who were managed nonoperatively. The rates of reoperation including subsequent ankle arthroscopy, ankle arthrodesis, and total ankle arthroplasty (TAA) were compared between groups. Results: 24,758 patients who underwent operative stabilization were matched to 24,758 patients who underwent nonoperative management for syndesmotic injury. Patients who underwent surgical stabilization had an increased risk of ankle arthrodesis (4.04; p< 0.001) and TAA (OR 3.11; p< 0.001) within ten years compared to patients managed nonoperatively. There was no difference between groups with regard to the comparative risk of subsequent ankle arthroscopy within five years. Conclusion: Patients with isolated syndesmotic injury who underwent operative stabilization were more likely to require an ankle arthrodesis or total ankle arthroplasty within 10 years compared to those who were managed nonoperatively. These findings in a large, propensity-matched cohort suggest that surgeons should consider the implications of syndesmotic over-reduction when managing these injuries intraoperatively. Moreover, surgeons may incorporate these data into the decision making process when counseling patients regarding the expected outcomes of operative and nonoperative management for syndesmotic injury.